The dynamics of digital banking adoption: Insights from Iran's context on marketing strategies and personal competence - Afshar Bazyar (goodwood publishing, 2024)
Purpose: This study investigates the factors affecting customers' digital banking adoption using the Technology Adoption Model (TAM), supplemented by Bank Marketing Activities (BMA) and Bank Personal Competence (BPC). Research Methodology: A total of 271 participants were analyzed quantitatively using Structural Equation Modeling (SEM) with IBM AMOS 26. Results: The findings indicate that both Bank Marketing Activities (BMA) and Bank Personal Competence (BPC) play significant roles in augmenting the perceived ease of use and usefulness of digital banking. Specifically, BPC demonstrates greater efficacy in enhancing ease of use, whereas BMA affects both ease of use and usefulness. Key components of effective bank marketing include personnel expertise, proactive service delivery, and the effective handling of customer dissatisfaction. Moreover, essential competencies for bank staff include being responsive, adept at problem solving, and adhering to ethical standards. Limitations: The applicability of this study's findings is primarily focused on the educational environment. Contribution: This study expands the theory of technology adoption, particularly within the realm of marketing functions. It offers valuable managerial insights into the prioritization of bank services and the development of personnel competencies aimed at bolstering the adoption of digital banking services.